2020
DOI: 10.2147/cmar.s268863
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long Non-Coding RNA USP2-AS1 Accelerates Cell Proliferation and Migration in Ovarian Cancer by Sponging miR-520d-3p and Up-Regulating KIAA1522</p>

Abstract: Background Ovarian cancer is one of the malignant tumors attacking the female reproductive system. Currently, increasing studies have clearly determined the importance of long non-coding RNAs (lncRNAs) in various human cancers including ovarian cancer. However, the role and in-depth mechanism of ubiquitin specific peptidase 2 antisense RNA 1 (USP2-AS1) in ovarian cancer have been not reported yet. Purpose We were absorbed into exploring the character of USP2-AS1 in ovar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…These results indicate that MAP3K3 mediates the effect of lncRNA CTBP1-DT in regulating the malignant biological behaviour of HGSOC cells in vivo. Previous studies have confirmed that lncRNA USP2-AS1 [ 28 ], HOXD-AS1 [ 29 ] and HEIH [ 24 ] are upregulated in OC, which can, in effect, promote the progression and development of OC cells by upregulating the expression of downstream target genes. LncRNA CTBP1-DT has been shown to elevate ZNF217 expression in cervical cancer [ 14 ] and regulate phosphatase and tensin homologue to suppress OC cell proliferation [ 30 ].…”
Section: Discussionmentioning
confidence: 95%
“…These results indicate that MAP3K3 mediates the effect of lncRNA CTBP1-DT in regulating the malignant biological behaviour of HGSOC cells in vivo. Previous studies have confirmed that lncRNA USP2-AS1 [ 28 ], HOXD-AS1 [ 29 ] and HEIH [ 24 ] are upregulated in OC, which can, in effect, promote the progression and development of OC cells by upregulating the expression of downstream target genes. LncRNA CTBP1-DT has been shown to elevate ZNF217 expression in cervical cancer [ 14 ] and regulate phosphatase and tensin homologue to suppress OC cell proliferation [ 30 ].…”
Section: Discussionmentioning
confidence: 95%
“…Among these biomarkers, only MKLN1-AS has been reported in HCC and is considered a diagnostic and prognostic biomarker (42). HPN-AS1 could be utilized in the diagnosis of prostate cancer (43); LINC00607 facilitates the proliferation and invasion of osteosarcoma (44); USP2-AS1 promotes the progression of colon cancer and ovarian cancer (45,46); and LINC00638 and LINC00652 have been reported in nontumor diseases (47)(48)(49)(50), while no study has revealed the function of the remaining lncRNAs. As a result, further exploration of these lncRNAs may improve insight into the molecules underlying HCC.…”
Section: Discussionmentioning
confidence: 99%
“…USP2-AS1 was observed to be a direct target of HIF1-α, and it is overexpressed in HNSCC, promoting cell proliferation and invasion through regulating DCAF13 activity ( 125 ). Additionally, USP2-AS1 was observed to be upregulated in ovarian cancer ( 126 ). It is a direct target of the transcription factor Myc, a key oncogene, promoting tumor progression through the regulation of E2F1 expression ( 127 ).…”
Section: Resultsmentioning
confidence: 99%